Response Surface Optimization of Hydrogen-Rich Syngas Production by Greenhouse Gases Reforming - Mageed A.K.; Ayodele B.V.; Mustapa S.I. (Wiley-VCH Verlag, 2023)
Carbon dioxide; Catalytic reforming; Greenhouse gases; Hydrogen; Methane; Partial pressure; Surface properties; Synthesis gas; Synthesis gas manufacture; CO2 reforming; Dry-methane reforming; Experimental values; Process interaction; Reforming of methane; Response surface methodology; Response surface optimization; Syngas production; Hydrogen production